L-plastin nanobodies perturb matrix degradation, podosome formation, stability and lifetime in THP-1 macrophages. - Sarah De Clercq; Ciska Boucherie; Joël Vandekerckhove; Jan Gettemans; Aude Guillabert (PLoS ONE)
Podosomes are cellular structures acting as degradation 'hot-spots' in monocytic cells. They appear as dot-like structures at the ventral cell surface, enriched in F-actin and actin regulators, including gelsolin and L-plastin. Gelsolin is an ubiquitous severing and capping protein, whereas L-plastin is a leukocyte-specific actin bundling protein. The presence of the capping protein CapG in podosomes has not yet been investigated. We used an innovative approach to investigate the role of these proteins in macrophage podosomes by means of nanobodies or Camelid single domain antibodies. Nanobodies directed against distinct domains of gelsolin, L-plastin or CapG were stably expressed in macrophage-like THP-1 cells. CapG was not enriched in podosomes. Gelsolin nanobodies had no effect on podosome formation or function but proved very effective in tracing distinct gelsolin populations. One gelsolin nanobody specifically targets actin-bound gelsolin and was effectively enriched in podosomes. A gelsolin nanobody that blocks gelsolin-G-actin interaction was not enriched in podosomes demonstrating that the calcium-activated and actin-bound conformation of gelsolin is a constituent of podosomes. THP-1 cells expressing inhibitory L-plastin nanobodies were hampered in their ability to form stable podosomes. Nanobodies did not perturb Ser5 phosphorylation of L-plastin although phosphorylated L-plastin was highly enriched in podosomes. Furthermore, nanobody-induced inhibition of L-plastin function gave rise to an irregular and unstable actin turnover of podosomes, resulting in diminished degradation of the underlying matrix. Altogether these results indicate that L-plastin is indispensable for podosome formation and function in macrophages.